An Analysis of Halal Regulation and Its Implications for MSMEs: A Systematic Literature Review - Awalludin, Taufiq; Tamamudin, Tamamudin; Sadali, Ayatullah (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2025)
This study aims to analyze halal regulations and their implications for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a systematic literature review approach. The halal regulations, established by Law Number 33 of 2014 concerning Halal Product Assurance, mandate businesses to comply with halal certification standards, directly impacting the dynamics of MSME operations. Using the PRISMA 2020-based systematic literature review method, this study identified and synthesized 40 selected scholarly articles from major databases such as Scopus, Google Scholar, and ScienceDirect. The analysis reveals that the implementation of halal regulations offers significant opportunities for MSMEs to enhance competitiveness, market access, and consumer trust, particularly in the rapidly growing domestic and global halal markets. However, notable challenges were also identified, including limited access to information, relatively high certification costs, and insufficient technical assistance from relevant institutions. These implications call for collaborative strategies between the government, certification bodies, and MSMEs to create an inclusive and sustainable halal ecosystem. This study contributes original insights to the literature by offering a critical synthesis of the dynamics surrounding halal regulation and evidence-based policy recommendations to strengthen the MSME sector. It is expected that this research will serve as a vital reference for policymakers, academics, and practitioners in optimizing the potential of the national halal sector. REFERENSI Ab Talib, M. S., & Hamid, A. B. A. (2014). Halal logistics and the impact on supply chain management: A conceptual framework. International Journal of Logistics Systems and Management, 17(3), 269–290. https://doi.org/10.1504/IJLSM.2014.059821 Ab Talib, M.S., & Hamid, A.B.A. (2014). Halal logistics in Malaysia: A SWOT analysis. Journal of Islamic Marketing, 5(3), 322–343. https://doi.org/10.1108/JIMA-03-2013-0018 Abd Rahman, A., Asrarhaghighi, E., & Ab Rahman, S. (2015). Consumers and halal cosmetic products: Knowledge, religiosity, attitude and intention. Journal of Islamic Marketing, 6(1), 148–163. https://doi.org/10.1108/JIMA-09-2013-0068 Alserhan, B. A. (2010). On Islamic branding: Brands as good deeds. Journal of Islamic Marketing, 1(2), 101–106. https://doi.org/10.1108/17590831011055842 Ambali, A. R., & Bakar, A. N. (2014). People's awareness on halal foods and products: Potential issues for policy-makers. Procedia - Social and Behavioral Sciences, 121, 3–25. https://doi.org/10.1016/j.sbspro.2014.01.1104 Awan, H.M., Siddiquei, A.N., & Haider, Z. (2015). Factors affecting Halal purchase intention: Evidence from Pakistan’s Halal food sector. Management Research Review, 38(6), 640–660. https://doi.org/10.1108/MRR-01-2014-0022 Bonne, K., & Verbeke, W. (2008). Religious values informing halal meat production and the control and delivery of halal credence quality. Agriculture and Human Values, 25, 35–47. https://doi.org/10.1007/s10460-007-9076-y Fauzia, A., & Latief, I. (2021). Biaya sertifikasi halal dan dampaknya terhadap UMKM pangan. Jurnal Manajemen Usaha Kecil, 9(3), 201–215. Golnaz, R., Zainalabidin, M., Mad Nasir, S., & Eddie Chiew, F. C. (2010). Non-Muslims’ awareness of halal principles and related food products in Malaysia. International Food Research Journal, 17(3), 667–674. Lada, S., Tanakinjal, G. H., & Amin, H. (2009). Predicting intention to choose halal products using Theory of Reasoned Action. International Journal of Islamic and Middle Eastern Finance and Management, 2(1), 66–76. https://doi.org/10.1108/17538390910946276 Mohayidin, M.G., & Kamarulzaman, Y. (2014). Halal logistics: the Malaysian perspective. Asia Pacific Journal of Marketing and Logistics, 26(4), 556–573. https://doi.org/10.1108/APJML-06-2013-0066 Muhammad, N., Leong, V.S., & Nadarajah, D. (2016). Halal food certification and business performance: The Malaysian food manufacturing industry. British Food Journal, 118(8), 1973–1987. https://doi.org/10.1108/BFJ-12-2015-0487 Norazah, M. S. (2015). Halal certification: A strategic marketing tool for small and medium enterprises (SMEs) in Malaysia. Procedia - Social and Behavioral Sciences, 172, 42–48. https://doi.org/10.1016/j.sbspro.2015.01.334 Page, M. J., McKenzie, J. E., Bossuyt, P. M., Boutron, I., Hoffmann, T. C., Mulrow, C. D., ... & Moher, D. (2021). The PRISMA 2020 statement: An updated guideline for reporting systematic reviews. BMJ, 372, n71. https://doi.org/10.1136/bmj.n71 Rachmawati, R., Nugroho, Y., & Prasetyo, E. (2020). Peluang ekspor produk halal Indonesia dalam meningkatkan daya saing UMKM. Jurnal Perdagangan Internasional, 12(1), 77–90. Rezai, G., Mohamed, Z., & Shamsudin, M.N. (2012). Non-Muslim consumers’ understanding of Halal principles in Malaysia. Journal of Islamic Marketing, 3(1), 35–46. https://doi.org/10.1108/17590831211206572 Riaz, M. N., & Chaudry, M. M. (2004). Halal Food Production. CRC Press. https://doi.org/10.1201/9780203490035 Sani, N.A.M., & Dahlan, H.A. (2015). A Holistic Halal Ecosystem for Malaysian SMEs: A Preliminary Insight. Procedia Economics and Finance, 37, 514–520. https://doi.org/10.1016/S2212-5671(16)30159-0 Snyder, H. (2019). Literature review as a research methodology: An overview and guidelines. Journal of Business Research, 104, 333–339. https://doi.org/10.1016/j.jbusres.2019.07.039 Tieman, M. (2011). The application of Halal in supply chain management: in-depth interviews. Journal of Islamic Marketing, 2(2), 186–195. https://doi.org/10.1108/17590831111139893 Tieman, M., Vorst, J.G.A.J., & Ghazali, M.C. (2012). Principles in halal supply chain management. Journal of Islamic Marketing, 3(3), 217–243. https://doi.org/10.1108/17590831211259727 Tieman, M. (2011). The application of halal in supply chain management: In-depth interviews. Journal of Islamic Marketing, 2(2), 186–195. https://doi.org/10.1108/17590831111139893 Tieman, M., van der Vorst, J. G. A. J., & Ghazali, M. C. (2012). Principles in halal supply chain management. Journal of Islamic Marketing, 3(3), 217–243. https://doi.org/10.1108/17590831211259727 Tranfield, D., Denyer, D., & Smart, P. (2003). Towards a methodology for developing evidence-informed management knowledge by means of systematic review. British Journal of Management, 14(3), 207–222. https://doi.org/10.1111/1467-8551.00375 Winarno, F. G., & Purwanti, T. (2021). Tantangan UMKM dalam implementasi sertifikasi halal: Analisis di Kota Bandung. Jurnal Industri dan Usaha Kecil, 16(2), 134–148. Winarno, F.G., & Purwanti, T. (2021). Tantangan UMKM dalam Implementasi Sertifikasi Halal: Analisis di Kota Bandung. Jurnal Industri dan Usaha Kecil, 16(2), 134–148. Wilson, J. A. J., & Liu, J. (2011). The challenges of Islamic branding: Navigating emotions and halal. Journal of Islamic Marketing, 2(1), 28–42. https://doi.org/10.1108/17590831111115222 Yusof, S.A.M., & Jusoh, W.J.W. (2013). Islamic branding: the understanding and perceptions of Muslim consumers in Malaysia. Asian Social Science, 9(10), 92–101. https://doi.org/10.5539/ass.v9n10p92